Parasites and vector-borne diseases disseminated by rehomed dogs - Wright, Ian (2021)
The Companion Vector-Borne Diseases (CVBD) World Forum is a working group of leading international experts who meet annually to evaluate current scientific findings and future trends concerning the distribution, pathogenesis, clinical presentation, diagnosis and prevention of vector-borne infections of dogs and cats. At the 14th Symposium of the CVBD World Forum in Trieste, Italy (March 25-28, 2019), we identified the need to (i) bring attention to the potential spread of parasites and vectors with relocated dogs, and (ii) provide advice to the veterinary profession regarding the importance of surveillance and treatment for parasites and vector-borne infections when rehoming dogs. This letter shares a consensus statement from the CVBD World Forum as well as a summary of the problem faced, including the role of veterinary professionals in parasite surveillance, causal issues, and the importance of interdisciplinary cooperation in addressing the problem. To limit opportunities for dissemination of parasites and vectors, whenever possible, underlying problems creating the need for dog rehoming should be addressed. However, when it is necessary to rehome dogs, this should ideally take place in the country and national region of origin. When geographically distant relocation occurs, veterinary professionals have a vital role to play in public education, vigilance for detection of exotic vectors and infections, and alerting the medical community to the risk(s) for pathogen spread. With appropriate veterinary intervention, dog welfare needs can be met without inadvertently allowing global spread of parasites and their vectors.